1993
DOI: 10.1029/92ja02397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sudden solar wind dynamic pressure changes at subauroral latitudes: Change in magnetic field

Abstract: The observations obtained during the International Magnetospheric Study (IMS) from the magnetometers of the IGS network extending from Cambridge, England, to Tromso, Norway, are used to study the response of subauroral current systems to sudden changes in solar wind dynamic pressure. Observations show that the response is very strong at subauroral latitudes. The preliminary response in the H component is a brief, small increase in the dayside morning sector and a decrease in the afternoon and night sectors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
2
28
1
Order By: Relevance
“…The International Monitor for Auroral Geomagnetic Effects (IMAGE) magnetometer chain, located postnoon between 1400 and 1500 MLT in Scandinavia, saw a positive change of nearly 100 nT, peaking near 1220 UT and then decaying (not shown). Similar to results reported by Le et al [1993], the prenoon responses observed by the magnetometer at Narsarsauq, Greenland, were negative.…”
Section: Hydrodynamic and Magnetohydrodynamic Coupling To The Magnetosupporting
confidence: 79%
See 1 more Smart Citation
“…The International Monitor for Auroral Geomagnetic Effects (IMAGE) magnetometer chain, located postnoon between 1400 and 1500 MLT in Scandinavia, saw a positive change of nearly 100 nT, peaking near 1220 UT and then decaying (not shown). Similar to results reported by Le et al [1993], the prenoon responses observed by the magnetometer at Narsarsauq, Greenland, were negative.…”
Section: Hydrodynamic and Magnetohydrodynamic Coupling To The Magnetosupporting
confidence: 79%
“…[59] A further consequence of the HPS-HCS passage is a sudden impulse in the northward magnetic field recorded by subauroral dayside ground magnetometers [e.g., Le et al, 1993;Russell and Ginskey, 1995], an ionospheric current response to the HPS density increase. The International Monitor for Auroral Geomagnetic Effects (IMAGE) magnetometer chain, located postnoon between 1400 and 1500 MLT in Scandinavia, saw a positive change of nearly 100 nT, peaking near 1220 UT and then decaying (not shown).…”
Section: Hydrodynamic and Magnetohydrodynamic Coupling To The Magnetomentioning
confidence: 99%
“…The differences between groups include, in our opinion, several aspects of the more generic "morning/afternoon asymmetry" proposed by previous analysis. Indeed, a visual inspection of the experimental observations reported in the scientific literature suggests that, as for the present case, the transition between structures with different characteristics of the H component typically occurs at later MLTs for higher latitudes (namely, in the early morning hours at ∼30 • -35 • , around noon at ∼55 • -60 • ; Le et al, 1993;Russell and Ginskey, 1995;Tsunomura, 1998). Our results also reveal that the different responses at different sites basically reflect a close correspondence between the magnetospheric and the ground signals which occur along an axis that progressively rotates from N/S (night events) to an E/W orientation (dawn events).…”
Section: Discussionmentioning
confidence: 99%
“…At subauroral latitudes (∼54 • -58 • ), the asymptotic response shows a different pattern, with strongly depressed (and even negative) values in the morning, and enhanced values in the afternoon (∼30 nT/(nPa) 1/2 ; Russell and Ginskey, 1995). Previous analysis of the latitudinal dependence of the asymptotic variation (H component) showed a negative gradient between ∼5 • -50 • , both in diurnal and nocturnal sectors (Le et al, 1993;Russell et al, 1994a, b); more recently, however, Francia and Lepidi (2002) found a positive gradient between ∼36 • -65 • , in the afternoon sector. On the other hand, since early investigations (Matsushita, 1962;Nishida and Jacobs, 1962) different waveforms of the H component were detected at different stations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation